Are Climate Change Policies Politically Costly? - Furceri, Davide (IMF Working Papers; Working Paper ;, 2021)
Are policies designed to avert climate change (Climate Change Policies, or CCPs) politically costly? Using data on governmental popular support and the OECD's Environmental Stringency Index, we find that CCPs are not necessarily politically costly: policy design matters. First, only market-based CCPs (such as emission taxes) generate negative effects on popular support. Second, the effects are muted in countries where non-green (dirty) energy is a relatively small input into production. Third, political costs are not significant when CCPs are implemented during periods of low oil prices, generous social insurance and low inequality.